Effects of porcine brain hydrolysate on impairment of cognitive learning ability in amyloid β(1–40)‐infused rats. (18th December 2018) - Liu, Yu‐Tse; Cheng, Fu‐Yuan; Takeda, Shiro; Lai, Kung‐Ming; Lin, Liang‐Chuan; Sakata, Ryoichi
Abstract: This study assessed whether administering porcine brain hydrolysate (PBH) ameliorates the impairment of spatial cognition learning ability in amyloid β (Aβ)‐infused rats. PBH was prepared using organic solvents (i.e., acetone and ethanol). Enzyme hydrolysates were derived from these PBH and the sequence of the Aβ peptide for infusion was selected. The results indicated the PBH, in particular EP (porcine brain extract with ethanol and protease N), demonstrated the potentials to reduce damage of neurodegenerative disorders in vitro and in vivo. The principal findings of this study indicate that PBH has prolyl endopeptidase inhibitory activity in vitro. Moreover, administering EP to Aβ(1–40)‐infused rats significantly improves their performance on reference, spatial performance, and working memory tests during water maze tasks; concurrent proportional decreases are also observed in malondialdehyde levels, acetylcholinesterase (AChE) activity, and Aβ accumulation levels in brain tissues. The PBH was suggested to ameliorate learning deficits associated with Alzheimer's disease by inhibition of lipid peroxidation in the brain of Aβ infused rat.